Memories of Europe in the Art From Elsewhere - Huyssen, Andreas (PORTO ARTE: Revista de Artes Visuais, 2019)
The contemporary arts contain and nurture the social lives of European memory, both in Europe and abroad. But European memory cannot be fortressed. It must include memories of Europe as they circulate elsewhere in the world. The lecture will focus on three contemporary artists (Doris Salcedo, William Kentridge, and Vivan Sundaram) whose work engages with memories of political violence in aesthetic forms imaginatively appropriated and transformed from the legacies of European and Transatlantic modernism.